Sample pre-treatment for measurement of 129I in radwastes - 최계천; 한선호; 지광용; 최기섭; Ke-Chon Choi; Sun-Ho Han; Kwang-Yong Jee; Ki-Seop Choi (Journal of nuclear fuel cycle and waste technology (Online), 2005)
원전에서 발생되고 있는 방사성폐기물 중 I의 정량을 위하여 시료의 특성에 맞는 최적의 시료 전처리 및 회수방법을 고찰하였다. 난용성시료 중 모의 잡고체와 수지에 함유된 요오드를 산침출법과 알칼리 용융방법으로 분리하여 회수율을 측정한 결과 , 의 회수율을 각각 나타내었다. 모의 농축폐액 중 1291를 pH 7의 음이온 수지에 흡착시켜 선택적으로 분리한 후 회수율을 측정한 결과 의 회수율을 나타내었다. 폐액 중 함유되어있는 고 농도의 붕소가 요오드 회수율에 미치는 영향을 조사한 결과 1,200 g/mL 이하의 붕소는 I의 분리 및 정량에 영향을 주지 않았다. 원전 내 현장시료인 폐수지 중 I 회수율을 칼럼용리방법으로 분리 후 측정한 결과 (RSD, )를 나타내었다. Many different kinds of radwastes are discharged from the nuclear power plants, and I is included in these radwastes. Recovery test of I was evaluated for different radwastes(dry active waste, sludge, spent resin and simulated evaporator bottom). Recovery of I for dry active waste by acid leaching with NaClO was and l291 for spent rein by alkali fusion method with KOH as a flux agent was ), respectively. iodide in simulated evaporator bottom containing a high concentration of borate was adsorbed with anion exchange resin at pH 7 phosphate buffer solution. Recovery of I for anion exchange resin was and not affected up to 1,200 g/mL (as a Boron). Recovery of I for the spent resin from nuclear power plant was .